Anglicismy užívané k vyjádření emocí v komunikaci na chatu - Svobodová, Diana (Acta Universitatis Lodziensis. Folia Linguistica, 2007)
The text deals with loanwords of English origin used within the chat communication to express emotions. The author mentions lots of examples of words and sentences belonging to many spheres and levels of the language that are used in their original English or adapted forms, and tries to explain reasons why the communicants (mainly young people) prefer words outside their native language in these situations.